PAINFUL THALASSEMIA : A REVIEW - Kaur, Rajinder; Kaur, Dilpreet (SCHOOL SCIENCE, 2010)
The term Thalassemia is a disorder, mainly prevalent among Mediterranean people, and was responsible for its naming. ‘Thalassa’ is a Greek word for the ‘Sea’, and ‘Haema’ is for ‘blood’. It was first identified by Cooley and Lee (1925), hence named ‘Cooley’ s Anaemia’.Thalassemia is an inherited blood disorder, passed down through generations through genes. The disorder is a result of the failure of formation of haemoglobin in red blood cells and consequently is causing anaemia (Forget and Cohen, 2005). Normally, red blood cells survive for 120 days but inThalassemia, red blood cell survival is reduced.Thalassemia is actually an inherited autosomal co-dominant disorder. In this, the genetic defect results in reduced rate of synthesis of one of the globin chains that make up of haemoglobin.